Perancangan Sistem Informasi Pengobatan Alternatif Ramuan Jawa “Jiwa Mulia” Berbasis Web - Mujito; Kusuma, Deryzal Prio Dwi; Asmanto, Budi (Jurnal Ilmiah Sistem Informasi (JISI), 2025)
The Javanese Herbal Alternative Medicine “Jiwa Mulia” is a traditional health practice that has been operating since 2004 and serves the community with various herbal therapies based on Javanese herbs. Until now, the administration and recording of patient medical records has been done manually, from registration to recording consultation results. This manual procedure causes various obstacles such as delays in patient services, duplication of patient data, the risk of lost files, and difficulties in tracking patient history. To overcome these problems, this study aims to design and develop a Web-Based Patient Registration and Medical Records Information System to support operational efficiency and improve service quality. The development method used is the Waterfall method, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The technology used includes the PHP programming language, the CodeIgniter framework, and a MySQL database. The resulting system has several main features, such as online patient registration, visit data management, digital medical record recording, report printing, and automatic queue management. Testing results using the Black Box method indicate that all system functions run according to the design and user needs. The implementation of this system accelerates services, improves data accuracy, minimizes the risk of information loss, and provides more modern, fast, and structured services for the Javanese Herbal Alternative Medicine “Jiwa Mulia”.